The effectiveness of communicative language teaching in EFL context - Kasimova N.F. (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the effectiveness of communicative language teaching in EFL context. On this way, research has been pointed out advantages and disadvantages as the whole. In conclusion both theoretical and practical aspects noted out by author while some vivid examples recommended for the future research.